Seismic Performance of an Underground Structure with an Inerter-Based Isolation System. (19th April 2023) - Chen, Qingjun; Zhang, Luqi; Zhang, Ruifu; Pan, Chao
Abstract : Existing isolation methods for seismic control of underground structures show that increasing the energy dissipation effect for isolation bearings tends to unfavorably add the relative deformation and force responses of the isolated columns. Exploring high-performance energy dissipaters is necessary for simultaneously controlling multiple performance indices of isolated underground structures. In this study, an inerter-based isolation system installed in a subway station is proposed to isolate columns and dissipate input energy benefited by its mass amplification and damping enhancement mechanisms. The inerter is a two-terminal relative-acceleration-related inertial device that can adjust structural inertial properties but scarcely increase actual physical mass. A method for the development of the user-defined inerter element is proposed and used because of the absence of inerter elements in existing finite element software. Then, the soil-underground structure model is established to simulate a typical subway station with the inerter-based isolation system used at the top of the column. Parameter studies together with design cases are conducted under horizontal and vertical input excitations with different frequency components. The results show that the inerter-based system can simultaneously control multiple performance indices of the subway station, including the relative deformation, shear force, bending moment of the central column, and the horizontal relative deformation of the isolation layer. Meanwhile, the inerter-based system can realize the high-efficiency energy dissipation control effect with low demands for damping due to the damping enhancement. A large proportion of energy is first absorbed by the inerter and then reserved by the kinetic and potential energy of the inerter-based system. Therefore, the proposed inerter-based isolation system is effective for enhancing columns and reducing lateral dynamic responses, which can prevent underground structures from collapsing.